Elevated atmospheric CO2 increases Eucalyptus urophylla S. T. Blake stem diameter by stimulating cell proliferation and reducing lignin deposition - Innocente, Patricia Sitta [UNESP]; Teixeira, Simone Padua; Balbuena, Tiago Santana [UNESP] (Soc Botanica Brasil, 2020)
In 2019, the atmospheric CO2 concentration exceeded the 415 ppm milestone for the first time in the human history. According to projections of the Intergovernmental Panel on Climate Change (IPCC), CO2 levels will continue to rise in the future, potentially affecting all living organisms. Plants with C3 metabolism may benefit from rising CO2 levels because the significant losses of photosynthesis, driven by photorespiration could be diminished under this scenario. This study addressed the anatomical changes in the sterns of young Eucalyptus urophylla plants induced through cultivation in elevated CO2 (eCO(2)). Plants cultivated under eCO(2) showed increased stem diameter (i.e., radial width of the secondary xylem, secondary phloem and cortex tissues). Periodic acid-Schiff (PAS)/Toluidine Blue staining suggested a decrease in the lignification content in the newly formed tissues of eCO(2) stimulated plants. Levels of caffeate/5-hydroxyferulate O-methyltransferase form 1 (COMT1), a lignin biosynthesis specific proteoform, were significantly reduced in stem sections, supporting our findings: eCO(2) induces plant growth, but reduces lignified tissues.
Keywords: carbon dioxide; climate change; Eucalyptus; lignin; plant stress; stem anatomy